Answer:
1:5
Step-by-step explanation:
Answer:
Antibodies.
Step-by-step explanation:
Hope this helped!
The first step was the combine the like terms; in this example he is subtracting the 3x on both sides of the =.
If you were to solve the equation it would look like this:
2x+6=3x-8
-3x -3x
-x+6=-8
-6 -6
-x=-14
/-1 /-1
x=14
Answer
Step-by-step explanation: example
5/(X+2). + 2/(X+1)
Common denominator. Is both (X+2)(X+1)
So the first fraction needs (X+1) since it already has (X+2) the second fraction needs ( X+2)
5(X+1). / (X+2)((X+1) +. 2/(X+2)/(X+1)
So multiply 5 with X then 5 with 1 and 2 times X and 2 times 2
5x+5 + 2x+4 / (X+2)((X+1)
Answer 7x+9/ (X+2)(X+1)